Changes in the Recruitment of Transylvanian Local Government Representatives (Lord Lieutenants and Prefects) During and After the First World War - PÁL, Judit (Studia Universitatis Babeș-Bolyai Historia, 2024)
The study explores the changes in the Transylvanian Lord Lieutenants’ corps during and after the First World War, using a prosopographical approach. The comparative analysis of the Lord Lieutenants’ and prefects’ corps in 1918-1919 aims to examine the impact of various political and regime changes on the recruitment of these high officials. In the autumn of 1918, one can already talk of a partial change of the elite, since part of the newly appointed Lord Lieutenants had a very different social and family background than their predecessors. When the political status of Transylvania changed, at the end of 1918 and in 1919, it brought further, more radical changes atop the administrative elite: the Hungarian Lord Lieutenants were replaced by Romanian prefects, who did have the necessary qualifications, but who had no prior experience in local government. Rezumat: Studiul explorează schimbările din corpul comiţilor supremi transilvăneni în timpul Primului Război Mondial şi imediat după aceea, folosind o abordare prosopografică. Analiza comparativă a comiţilor supremi şi a prefecţilor din 1918-1919 are ca scop examinarea impactului diferitelor schimbări politice şi de regim asupra recrutării acestor înalţi funcţionari. În toamna anului 1918, se poate vorbi deja de o schimbare parţială a elitei, deoarece o parte dintre comiţii supremi nou numiţi aveau un mediu social şi familial foarte diferit de cel al predecesorilor lor. Când statutul politic al Transilvaniei s-a schimbat, la sfârşitul anului 1918 şi în 1919, a adus alte schimbări, mai radicale, la vârful elitei administrative: comiţii supremi maghiari au fost înlocuiţi cu prefecţi români, care aveau într-adevăr calificările necesare, dar care nu aveau experienţă anterioară în administraţia locală. Cuvinte cheie: comite suprem, prefect, elite şi schimbare, Transilvania, 1918, Primul Război Mondial Article: history; Received: 21.09.2023; Revised: 29.10.2023 Accepted: 03.11.2023; Available online: 30.01.2024